Bioactive edible films for food applications:Influence of the bioactive compounds on film structure and properties. Issue 7 (12th April 2019) - Benbettaïeb, Nasreddine; Karbowiak, Thomas; Debeaufort, Frédéric
ABSTRACT: Nowadays, a new generation of edible films is being especially designed for incorporating antimicrobials, antioxidants, enzymes or functional ingredients. Edible films made from natural biopolymers become the focus of many research works as an alternative to synthetic food packaging due to their edibility, biodegradability and compostability as well as to their use as active packaging. Active compounds incorporated in edible films could protect foods against deterioration during storage and therefore extend their shelf life. These active films were mainly studied for the bioactivity, as antimicrobial or antioxidant. However, they could also improve the structure and the physicochemical properties of films through chemical linkage with reactive groups of the polymer chains for instance. Moreover, changing the film structure under cross-linking reaction may increase the cohesion between polymer chains and active compounds, and therefore their retention in the polymer network to better control their release. This manuscript provides an overview on the effect of bio-active compounds incorporation on the film structure and functional properties. Depending on their structure, concentration, reactive groups, .., active compounds can act as plasticizer, but also as anti-plasticizer or cross-linking agents in the biopolymer matrix, and can thus ameliorate the water vapour and gas permeability. Therefore, the retention of bioactive compounds in the polymer network and their release can be better controlled. They can also provide a negative plasticizing effect on the film structure. Hence, the improvement of edible active film functionalities has been investigated to achieve suitable applications on foods.